Practitioner perspectives on the application of palaeoecology in nature conservation - Siggery, Ben; Bennion, Helen; Morse, Stephen; Murphy, Richard; Waite, Mike (Frontiers in Ecology and Evolution, 2023)
It is widely recognised that palaeoecology holds great potential to inform and support nature conservation, but that there are difficulties in knowledge exchange between academia and practitioners that inhibit the operationalisation of research. To facilitate the integration of palaeoecology into the conservation toolkit, it is essential to understand perspectives of the practitioners themselves and the contexts in which they work. This paper reports the results of a survey of 153 UK-based conservation practitioners, concerning their perceptions of palaeoecology, the barriers to its use and potential solutions for making palaeoecological insights more accessible in conservation practice. The majority of respondents were strongly positive about the role palaeoecological research could play, though they also exhibited a limited understanding of how and why one might implement it. They identified time constraints as the biggest barrier to using palaeoecology within their work, and also flagged concerns around financial resources and the accessibility of the research. Access to applied case studies and a centralised database were the most favoured solutions among respondents. Respondents with prior experience of working with palaeoecology were generally more optimistic about its incorporation. This paper makes several key recommendations to progress the integration of palaeoecology into conservation, including improving data accessibility, aligning research design with conservation and policy drivers, and increasing both respective groups' understanding of the other.